Нова версiя Q-деформованої суперсиметричної квантової механiки - Gavrilik, A. M.; Kachurik, I. I.; Lukash, A. V. (Publishing house "Academperiodika", 2018)
A new version of the q-deformed supersymmetric quantum mechanics (q-SQM), which is inspired by the Tamm–Dankoff-type (TD-type) deformation of quantum harmonic oscillator, is constructed. The obtained algebra of q-SQM is similar to that in Spiridonov’s approach. However, within our version of q-SQM, the ground state found explicitly in the special case of superpotential yielding q-superoscillator turns out to be non-Gaussian and takes the form of special (TD-type) q-deformed Gaussian.